Digital Collections Service for the ROSSIO Infrastructure - Coelho, Luís Duarte Carrilho (2022)
Nowadays, especially during these challenging pandemic times, the need to have valuable cultural assets preserved online and available for current and future generations has grown exponentially. Cultural and educational sectors faced unprecedented obstacles as a result of the pandemic’s containment measures since many physical places such as schools, libraries, and museums had little choice but to close temporarily. Digital media has played a vital role in people’s daily interactions and was essential for the affected sectors to continue their work remotely. The pandemic has given an opportunity for cultural heritage organizations to show the benefits of digital collections and resources. By increasing access to a multitude of resources, spotlighting "hidden gems", preserving content, giving students digital materials to learn from, and providing users a different view on cultural heritage, the digital libraries and their digital collections have demonstrated how much they can enable a rich and diverse public domain. This Master’s dissertation was developed in collaboration with the ROSSIO infrastruc- ture, intending to create a service for their platform that allows the creation of digital collections made up of cultural heritage resources gathered by ROSSIO and its partner institutions. The developed service aims to give authenticated users access to an intuitive interface that includes the tools they need to create, edit, and share collections with the public, showcasing the best of Portugal’s cultural heritage in thematic collections that anyone can explore, enjoy and share.